2003
DOI: 10.1037/0096-1523.29.2.333
|View full text |Cite
|
Sign up to set email alerts
|

Change deafness: The inability to detect changes between two voices.

Abstract: A shadowing task was used to demonstrate an auditory analogue of change blindness (the failure to detect a change in a visual scene), namely change deafness. Participants repeated words varying in lexical difficulty. Halfway through the word list, either the same or a different talker presented the words to participants. At least 40% of the participants failed to detect the change in talker. More interesting is that differences in shadowing times were found as a function of change detection. Alternative possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
95
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(107 citation statements)
references
References 50 publications
(98 reference statements)
10
95
2
Order By: Relevance
“…This general interest stems from the fact that change blindness demonstrates the crucial role of visual attention and visual memory in determining the contents of conscious visual perception (Mack & Rock, 1988;Rensink, 2002; see also Gallace, Auvray, et al, 2006;, for examples in the tactile modality). Two recent studies have addressed whether an analogue of change blindness exists in the auditory domain and have shown that changes in auditory scenes can be missed with remarkable ease when not attended (Eramudugolla et al, 2005;Vitevitch, 2003), a phenomenon that the investigators termed change deafness. Eramudugolla et al (2005) explicitly linked the observed phenomenon to the 500-msec white-noise interval they had introduced between the two auditory scenes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This general interest stems from the fact that change blindness demonstrates the crucial role of visual attention and visual memory in determining the contents of conscious visual perception (Mack & Rock, 1988;Rensink, 2002; see also Gallace, Auvray, et al, 2006;, for examples in the tactile modality). Two recent studies have addressed whether an analogue of change blindness exists in the auditory domain and have shown that changes in auditory scenes can be missed with remarkable ease when not attended (Eramudugolla et al, 2005;Vitevitch, 2003), a phenomenon that the investigators termed change deafness. Eramudugolla et al (2005) explicitly linked the observed phenomenon to the 500-msec white-noise interval they had introduced between the two auditory scenes.…”
Section: Discussionmentioning
confidence: 99%
“…also Gallace, Auvray, Tan, & Spence, 2006, for a visuotactile version of the paradigm). The existence of change deafness has also been described: A listener's ability to detect a change in the auditory scene declines systematically as the complexity of the scene increases-specifically, when attention cannot be directed to the changing feature or object in advance (Eramudugolla, Irvine, McAnally, Martin, & Mattingley, 2005; see also Vitevitch, 2003).…”
Section: University Of Trento Rovereto Italymentioning
confidence: 99%
See 1 more Smart Citation
“…In vision, change blindness, which is where people fail to see major changes in a scene as the result of a distractor, or from coincidence with a blink or a saccade, has been extensively studied [65,72]. A similar phenomenon exists for audition, change deafness [78]. It is thus natural that something analogous should occur for touch, and indeed, it does with distractors which are either tactile or visual [29,30].…”
Section: Change Numbnessmentioning
confidence: 99%
“…Saccadic or flash suppression is quite distinct from a variety of other effects which can be classified under the collective name of change blindness (or change deafness, or even change numbness) whereby a change in a scene is not seen (or heard or felt) if that change occurs during a disruption (Rensink et al, 1997, Vitevitch, 2003, Gallace et al, 2006. In "change x-ness", the conditions are such that massive changes in the stimulation are blocked from reaching the conscious experience as the result of an attentional effect, eliciting considerable surprise once the participants are subsequently made aware of them.…”
Section: Related Effectsmentioning
confidence: 99%